Processing of Hyperspectral Medical Images Applications in Dermatology Using Matlab® - Koprowski, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents new methods of analyzing and processing hyperspectral medical images, which can be used in diagnostics, for example for dermatological images. The algorithms proposed are fully automatic and the results obtained are fully reproducible. Their operation was tested on a set of several thousands of hyperspectral images and they were implemented in Matlab. The presented source code can be used without licensing restrictions. This is a valuable resource for computer scientists, bioengineers, doctoral students, and dermatologists interested in contemporary analysis methods.
Processing of Hyperspectral Medical Images: Applications in Dermatology Using Matlab® -- Foreword -- Preface -- Acknowledgments -- List of selected symbols -- Chapter1: Introduction -- Chapter2: Image acquisition -- Chapter3: Image pre-processing -- Chapter4: Image processing -- Chapter5: Classification -- Chapter6: Sensitivity to parameter changes -- Chapter7: Conclusions -- Appendix -- References -- Summary.
Keywords: Computational intelligence; Artificial intelligence; Dermatology; Computational Intelligence; Artificial Intelligence; Dermatology